Evaluating core stability training-based combination therapies for lower extremity dysfunction post-stroke: a systematic review and network meta-analysis - Kaiqi Zheng; Liang Guo; Dan Wang; Chunyun Deng (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Stroke is a severe neurological disorder that poses a significant threat to patients’ health and imposes a heavy burden on healthcare resources. This study aims to systematically evaluate the synergistic effects of core stability training combined with various rehabilitation interventions to identify the optimal treatment strategy for lower extremity dysfunction in stroke patients, providing stronger evidence for clinical practice. Methods This study included randomized controlled trials (RCTs) published before May 12, 2025. The included studies met the following criteria: Participants were stroke patients with lower extremity dysfunction; The intervention in the experimental group involved core stability training or core stability training combined with other rehabilitation measures; The control group received either core stability training alone or conventional rehabilitation treatment; Outcome measures included balance ability, functional mobility, lower extremity motor ability, and walking ability; Study design was RCT. We searched six databases, including PubMed, Embase, Cochrane Library, Web of Science, CNKI (China National Knowledge Infrastructure), and SinoMed (China Biology Medicine), and conducted a network meta-analysis using R studio and Stata 15.0. We used the Risk of Bias 2.0 (ROB 2.0) tool to assess the risk of bias in the included studies. Results For balance ability in stroke patients, the rehabilitation effect of neuromuscular electrical stimulation combined with core stability training (NMES + CST) seemed to be the most effective, with a surface under the cumulative ranking curve (SUCRA) of 90.82%. For functional mobility of lower extremity in stroke patients, proprioceptive training combined with core stability training (PT + CST) appeared to show the best rehabilitation effect (SUCRA = 93.24%). For motor ability of lower extremity, acupuncture therapy combined with core stability training (AT + CST) seemed to be the most effective (SUCRA = 90.83%). For walking ability, motor imagery training combined with core stability training (MIT + CST) seemed to be the optimal rehabilitation effect (SUCRA = 93.87%). Cluster analysis results indicated that the optimal treatment regimens for stroke-induced lower extremity dysfunction were PT + CST (SUCRA = 58.29%/SUCRA = 93.24%/ SUCRA = 63.59%/SUCRA = 56.03%) and AT + CST(SUCRA = 65.62%/SUCRA = 90.83%/SUCRA = 60.25%). Conclusions NMES + CST, PT + CST, AT + CST, and MIT + CST are four effective core stability training combination therapies. Comprehensive evaluation results indicate that AT + CST or PT + CST seems to be the optimal core stability training combination therapy for lower extremity dysfunction in stroke patients. Registration PROSPERO CRD42024588917.